Manilius on the nature of the Universe - Colborn, R (2015)
The thesis has two aims. The first is to show that a more charitable approach to Manilius, such as Lucretian scholarship has exhibited in recent decades, yields a wealth of exciting discoveries that earlier scholarship has not thought to look for. The thesis' contributions to this project centre on three aspects of the poem: (I) the sophistication of its didactic techniques, which draw and build on various predecessors in the tradition of didactic poetry (II) its cosmological, physical and theological basis, which has no exact parallel elsewhere in either astrology or natural philosophy, and despite clear debts to various traditions, is demonstrably the invention of our poet (III) the extent to which rationales and physical bases are offered for points of astrological theory – something unparalleled in other astrological texts until Ptolemy. The second, related aim of the thesis is to offer a more satisfying interpretation of the poem as a whole than those that have hitherto been put forward. Again the cue comes from Lucretius: though the DRN is at first sight primarily an exposition of Epicurean physics, it becomes clear that its principal concern is ethical, steering its reader away from superstition, the fear of death and other damaging thought-patterns. Likewise, the Astronomica makes the best sense when its principal message is taken to be not the set of astrological statements that make up its bulk, but the poem’s peculiar world- view, for which those statements serve as an evidential basis. It is, on this reading, just as much a poem ‘on the nature of the universe', which provides the title of my thesis. At the same time, however, it finds new truth in the conventional assumption that Manilius is first and foremost an advocate of astrology: it reveals his efforts to defend astrology at all costs, uncovers strategies for making the reader more amenable to further astrological study and practice, and contends that someone with Manilius' set of beliefs must first have been a devotee of astrology before embracing a natural- philosophical perspective such as his. The thesis is divided into prolegomena and commentaries, which pursue the aims presented above in two different but complementary ways. The prolegomena comprise five chapters, outlined below: Chapter 1 presents a comprehensive survey of the evidence for the cosmology, physics and theology of the Astronomica, and discovers that a coherent and carefully thought-out world-view underlies the poem. It suggests that this Stoicising world- view is drawn exclusively from a few philosophical works of Cicero, but is nonetheless the product of careful synthesis. Chapter 2 explores the relationship between this world-view and earlier Academic criticism of astrology and concludes that the former has been developed as a direct response to these criticisms, specifically as set out in Cicero’s De divinatione. Chapter 3 examines the later impact of Manilius’ astrological world-view, as far as it can be detected, assessing the evidence for the early reception of his poem and its role in the history of philosophical astrology. The overwhelming impression is that the work was received as a serious contribution to debate over the physical and theological underpinnings of astrology; its world-view was absorbed into the mainstream of astrological theory and directly targeted in the next wave of Academic criticism of astrology. Chapter 4 looks at the more subtle strategies of persuasion that are at work in the Astronomica. It observes, first, a number of structural devices and word- patternings that set up the poem as a model of the universe it describes. This first part of the chapter concludes by asking what didactic and/or philosophical purpose such modelling could serve. The second part examines how, by a gradual process of habituation-through-metaphor, the reader is made familiar with the conventional astrological way of thinking about the world, which might otherwise have struck him as a baffling mass of contradictions. The third part looks at the use of certain rhetorical figures, particularly paradox, to re-emphasise important physical claims and assist the process of habituation. Chapter 5 takes on the task of making sense of the Astronomica as a whole, seeking out an underlying rationale behind the choice and ordering of material, accounting as well as is possible for its apparently premature end, and asking why, if it is a serious piece of natural-philosophical teaching, it so often appears to be self- undermining. A short epilogue asks what path can have led Manilius to embark on such a work as the Astronomica. It offers a sketch of the author as an adherent (but not a practitioner) of astrology, who had developed a philosophical system first as scaffolding for an art under threat, but had then come to see more importance in that philosophical underpinning than in the activities of prediction. The lemmatised commentaries that follow cover several passages from the first book of the Astronomica. As crucial as the remaining four books are to his natural-philosophical teaching, it is in this part of the poem that Manilius concentrates the direct expositions of his world-view. Like the chapters, the commentaries' two concerns are the nature and the exposition of the work's world-view. Each of the commentaries has its own focus, but all make full use of the format to tease out the poet's teaching strategies and watch his techniques operate 'in real time' over protracted stretches of text. Finally, an appendix presents the case for the Astronomica as the earliest evidence for the use of plane-image star maps. At two points in his tour of the night sky Manilius describes the positions of constellations in a way that suggests that he is consulting a stereographic projection of each hemisphere, and that he is assuming his reader has one to hand, too. This observation casts valuable new light on the development of celestial cartography.